DEBT BURDEN SHIFTING AND WELFARE LOSS IN COUNTRIES UNDER DEBT TRAP - Alam, Noor; Taib, Fauzia (European Scientific Journal, ESJ, 2012)
The government spending on development sector plays a significant role towards economic growth as it is the most powerful economic agent in all modern societies. The main objective of this paper is to explain theoretically the phenomenon of unique debt burden shifting and welfare loss in countries under debt trap with the support of descriptive statics of a panel of fourteen, Asian Pacific Developing Countries (APDC). This paper is an extension of our previous paper on debt trap and basic borrowing fundamentals (see Alam & Taib, 2012). The analysis shows that the government spending on development sector plays significant role towards economic performance of the country and improves welfare of its citizens. Any decrease in government development spending affects country‟s economy negatively and hurts welfare of the citizens. It provides guidelines for the policy makers on choice between debt and tax especially in the servicing of public debt.